Determinar los requerimientos hídricos del pepino (Cucumis sativus L) mediante el lisímetro volumétrico, en el sector Trinidad perteneciente al sistema de riego Campana-Malacatos. - Martínez Sánchez, Yandry Paúl (2017)
The objective of the present study was to determine the water requirements of cucumber (Cucumis Sativus L), using volumetric lysimeters, belonging to the system of irrigation campaign Malacatos Trinity sector, whose height is between 1400-1470 msnm. Campaign-Malacatos irrigation system is located at three altitudes, where the floor bass and medium have a climate tempered with an annual average temperature of 18 ° C and the upper floor with a temperate climate with an annual average temperature of 14 ° C. The considered phenological stages were: germination and initial growth, initial phase; (0-18 days), development of the crop (19-49 days), mid (50-73 days) period and late period or harvest (59-70 days); for a cycle of cultivation of ninety-five (95 days) days from sowing up to the last harvest. The planting area was 33,84 m2, which featured two lysimeters 1m 2 each. The crop that I start in the whole area was cucumber variety marketmore76 with a stocking density of 0.35 x 0.60. The reference evapotranspiration calculated by the method of Penman Monteith determined that the highest value of ETo arises for the phase of development of the cultivation of cucumber of 5.21 phenological period mm/day. While the lower value occurs in the initial phase of 4.41 mm/day. While cucumber crop evapotranspiration was determined that the highest value etc arises for the development phase of 3.29 mm/day. While the lower value occurs in the initial phase of 2.15 mm/day. The estimation of the water needs of crops is one of the stages required in the design, construction, installation and operation of any irrigation system that you want to deploy. Is why the values of coefficient of cucumber crop estimates for the phenological periods of cucumber cultivation are: germination, initial growth, or 0.49 initial phase, development of farming 0.63, mid period 0.64 and end of the period or harvest 0.57.